ANALISIS PENERAPAN STANDAR OPERASIONAL PROSEDUR BUDIDAYA UNTUK PENGENDALIAN KUALITAS HASIL PANEN JAGUNG - Dwi Putra, Achmad Ivan; Surianto, Moh Agung (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2021)
This research was conducted at PT. Agro Aku Bisa Jember, East Java. The aims of this study were (1) to analyze the application of standard operating procedures on corn farming at PT. Agro Aku Bisa Jember; (2) the effectiveness of the implementation of Quality Control of corn farming at PT. Agro Aku Bisa Jember. The basic method used is descriptive with a case study implementation. Data were collected by interview, observation and documentation methods. The results showed that (1) the application of standard operating procedures had been carried out well in planting to harvesting based on the following principles; (a) pre-planting land maintenance; (b) periodic land maintenance.